A Coupled Level Set and Volume of Fluid method for automotive exterior water management applications. (May 2017) - Dianat, M.; Skarysz, M.; Garmory, A.
Highlights: A Coupled Level-set Volume of Fluid method for unstructured meshes is implemented. Contact angle boundary condition implemented to allow simulation of surface flows. Method gives superior accuracy compared to VOF solver for cases presented. Excellent agreement found with experiment for a droplet impinging on a solid plate. Abstract: Motivated by the need for practical, high fidelity, simulation of water over surface features of road vehicles a Coupled Level Set Volume of Fluid (CLSVOF) method has been implemented into a general purpose CFD code. It has been implemented such that it can be used with unstructured and non-orthogonal meshes. The interface reconstruction step needed for CLSVOF has been implemented using an iterative 'clipping and capping' algorithm for arbitrary cell shapes and a re-initialisation algorithm suitable for unstructured meshes is also presented. Successful verification tests of interface capturing on orthogonal and tetrahedral meshes are presented. Two macroscopic contact angle models have been implemented and the method is seen to give very good agreement with experimental data for a droplet impinging on a flat plate for both orthogonal and non-orthogonal meshes. Finally the flow of a droplet over a round edged channel is simulated in order to demonstrate the ability of the method developed to simulate surface flows over the sort of curved geometry that makes the use of a non-orthogonal grid desirable.